2017
DOI: 10.1145/3138805
|View full text |Cite
|
Sign up to set email alerts
|

Could Compression Be of General Use? Evaluating Memory Compression across Domains

Abstract: Recent proposals present compression as a cost-effective technique to increase cache and memory capacity and bandwidth. While these proposals show potentials of compression, there are several open questions to adopt these proposals in real systems including the following: (1) Do these techniques work for real-world workloads running for long time? (2) Which application domains would potentially benefit the most from compression? (3) At which level of memory hierarchy should we apply compression: caches, main m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Sardashti and Wood [68] observed that cachelines in the same page may not have similar compressibility. Hallnor et.…”
Section: F Other Relevant Workmentioning
confidence: 99%
“…Sardashti and Wood [68] observed that cachelines in the same page may not have similar compressibility. Hallnor et.…”
Section: F Other Relevant Workmentioning
confidence: 99%